2021
DOI: 10.1155/2021/5516368
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based on Residual Networks for Automatic Sorting of Bananas

Abstract: This study presents the design of an intelligent system based on deep learning for grading fruits. For this purpose, the recent residual learning-based network “ResNet-50” is designed to sort out fruits, particularly bananas into healthy or defective classes. The design of the system is implemented by using transfer learning that uses the stored knowledge of the deep structure. Datasets of bananas have been collected for the implementation of the deep structure. The simulation results of the designed system ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Machine learning has been a crucial "catalyst" in the 60 years of development. Machine learning is to make the computer learn repeatedly to improve its performance and intelligently identify new samples through relevant algorithms, so that the computer can make correct responses and behaviors without explicit programming control [4]. In the past decade, machine learning has been widely applied in various fields such as autonomous driving, speech recognition, data mining, medical diagnosis, weather forecast, and industrial control.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning has been a crucial "catalyst" in the 60 years of development. Machine learning is to make the computer learn repeatedly to improve its performance and intelligently identify new samples through relevant algorithms, so that the computer can make correct responses and behaviors without explicit programming control [4]. In the past decade, machine learning has been widely applied in various fields such as autonomous driving, speech recognition, data mining, medical diagnosis, weather forecast, and industrial control.…”
Section: Introductionmentioning
confidence: 99%
“…In (7) , the researchers used a 9-layer convolutional neural network with data augmentation for the classification of fruits. It showed that with data augmentation they obtained an average precision of 96.34%.The architecture of a deep learning structure for rating bananas as healthy or defective is shown in the study (8) . The "ResNet-50" residual learning-based network was created to sort bananas.…”
Section: Introductionmentioning
confidence: 92%
“…Pu et al proposed a method for identifying the origins of tangerine peel using terahertz timedomain spectroscopy combined with CNN (convolutional neural network) [14]. Diferent spectral data were used to Deep learning [15] is a machine learning technique in which machines simulate the human brain to analyze data, with the computer vision [16] being one of the more prominent applications. In the past few years, the image classifcation of agricultural products represented by tangerine peel is emerging.…”
Section: Related Workmentioning
confidence: 99%